2022
DOI: 10.1007/s11356-022-22885-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel lens of stock market capitalization and environmental degradation

Abstract: This research article examines the impact of stock market capitalization on carbon emissions using forty high carbon-emitting countries from 1996 to 2018. This study adopts the Driscoll-Kraay method that simultaneously tackles heteroscedasticity, autocorrelation, and contemporaneous correlation issues. We find an inverted U relationship between stock market capitalization (SMC) and environmental degradation. We propose an extended environmental Kuznets curve based on SMC while energy intensity, industrializati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Additionally, research has looked into how stock market capitalization affects the funding and promotion of green projects. The development of green businesses and technology can be aided by a healthy stock market's ability to draw money and investments for sustainable initiatives (Azeem et al 2023). Initial public offers (IPOs) and secondary offerings on the stock market may also affect the availability of nance for renewable energy projects (Alam et al 2021).…”
Section: )mentioning
confidence: 99%
“…Additionally, research has looked into how stock market capitalization affects the funding and promotion of green projects. The development of green businesses and technology can be aided by a healthy stock market's ability to draw money and investments for sustainable initiatives (Azeem et al 2023). Initial public offers (IPOs) and secondary offerings on the stock market may also affect the availability of nance for renewable energy projects (Alam et al 2021).…”
Section: )mentioning
confidence: 99%
“…Among the foreign colleagues who partially touched on the problem declared in the article is Gunawan and SE (2018), Nurhayati et al (2021). For example, Kuvshinov and Zimmermann (2022) emphasize the study of long-term trends in the market capitalization of listed firms and their drivers, because, according to them, the unique advantage of focusing on listed companies is that we can obtain highquality data, necessary to analyze the development of the corporate sector over very long periods of time in many countries. Also, considering issues of market power from different points of view, the role of market capitalization and intellectual capital in determining corporate investment decisions, the importance of stock markets that unite all parties to pool resources and increase economic activity were emphasized by Syverson (2019), Farooq et al (2022), Azeem et al (2022), Bazaluk et al (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bai et al, (2021) categorize stock exchanges as crucial and leading indicator in its role, on the other hande Altan et al, (2021) discussed financial markets and found worthy in market capitalization. It is thought to be the utmost effective stock market valuation indicator which ulyimwtely boosts up investors' assurance (Azeem et al, 2023).…”
Section: Introductionmentioning
confidence: 99%